Drinking intoxicating liquor or alcohol: the shariah punishment and with reference to the case of Kartika Sari Dewi Shukarno - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (Malayan Law Journal Sdn Bhd, 2009)
This article will consider the recent decision of the Shariah High Court in Kuantan in relation to the case of Kartika Sari Dewi Shukamo which had received widespread condemnation both from the local and the international community. In Kartika's case, the accused pleaded guilty to the charge of consuming alcohol and was sentenced to six strokes of the cane and a fine of RM5, 000. She accepted the sentence and was adamant that the canning be carried out and that too, in public. Many were however outraged by the severity of the punishment. Among the comments were, inter alia, that the sentence was rather 'cruel, inhumane, degrading and prohibited by the international human right laws'; its administration was rather cruel against women; corporal punishment for Shariah offences must be the last resort against women; as a first time offender, she should not have received the maximum sentence; imposition of fine together with whipping was inappropriate and that canning does not deter rnisbehaviour. Some argued that the negative publicity of the case will affect the Malaysian long standing reputation as a moderate Muslim state and inevitably, the economy of the country. Some have urged the relevant authority to abolish canning from the statute books for consuming alcohol. The Prime Minister of Malaysia had even urged Kartika to appeal against the decision and some have stated that this was sufficient to authorise the Shariah Appeal Court to take the case for review. Some found no wrong in drinking alcohol, among others. This article will therefore, analyse some of these criticisms.